The perceived effectiveness of blockchain for digital operational risk resilience in the European Union insurance market sector - Simon Grima; Murat Kizilkaya; Kiran Sood; Mehmet ErdemDelice (Journal of Risk and Financial Management, 2021)
Due to the rise in the demand for information communication technologies (ICT), the need for operational risk resilience within the European insurance market sector has grown exponentially. This study aims to use the case of blockchain to evaluate whether the five characteristics determined from the literature to be required for effective digital risk resilience (specifically, integration, flexibility, reliability, relevance, and timeliness) have an impact on effectiveness in addressing the requirements of the European Union's proposed Digital Operational Resilience Act (DORA). To achieve this, we developed a survey with 29 statements, which participants were required to answer using a five-point Likert scale. In total, 513 valid responses were received from participants. These were analyzed using exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and structural equation modeling (SEM). Results show that in the case of blockchain, reliability, flexibility, and relevance were found to significantly relate to its effectiveness in addressing DORA's requirements, but relationships of effectiveness with integration and timeliness were found to be insignificant. However, when the experience variable was added to the model as the moderator variable, we found that timeliness and relevance have a significant relationship with blockchain effectiveness, while integration, reliability, and flexibility do not.
Keywords: 330; blockchain; European 4; insurance market sector; operational risk resilience